THE APPLICATION OF RISK-BASED NEW VENTURE VALUATION TO CALCULATE VALUE OF HEALTHCARE START-UP (CASE STUDY : MED-EASE) - Buna Kristianto, Priskilla
During the COVID-19 pandemic, the Indonesian market's biggest growth rates were in the healthcare and technology sectors. As a new digital start-up that serves the healthcare sector, Med-Ease seized the opportunity to develop a business strategy. Med- Ease is a comprehensive web platform that helps healthcare organizations by supplying real-time data to improve patient care. At the moment, Waiting Ticket and Available Doctor are the two key characteristics that Med-Ease uses to service its consumers. On December 9, 2021, the Med-Ease web-based system went live at www.medease.id and began operating. By the end of Quadrant I in 2022, the company has achieved milestones 1 (prototyping and a market feasibility assessment) and 2 (beta testing and the generation of first revenue). In order to reach milestone 3 (acquiring a sales channel), Med-Ease needs to allocate additional money for marketing and sales efforts. We should not dismiss the role that a cash-burning marketing plan is expected to perform in this stage as an entrepreneur. The startup cannot rely on its current financing resources to get through the stage and avert cash flow problems. Med-Ease should therefore perform a start-up valuation to determine the company's value in order to obtain capital support from outside sources with the intention of realizing and expanding the business. The limited financial historical data and uncertain future, however, impose limitations on the new firm appraisal process. As a result, this study is being conducted to determine the selling price of Med-Ease to recommend to investors, taking into account its existing valuation at milestone 3 and its projection for milestone 4 (normal risk).